Improving employee performance: The role of self-efficacy and motivation - Muttaqin, Ridlwan; Indrianti, Resa Putri; Siddiq, Andhika Mochamad; Wijaya, Fanji; Jaya, Rama Chandra; Abdulrahman, Al Shikhy (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2023)
The rapid advancement of information technology has changed the positive mindset of employees in improving performance. The purpose of this study was to analyze the effect of self-efficacy on work motivation and its impact on employee performance at PT Pungkook Indonesia One. This research was conducted in November 2022 - February 2023 by distributing questionnaires online to respondents selected by purposive sampling with a total of 100 people and questionnaire data using the Amos Graphic tool. This study found that self-efficacy has a positive effect on work motivation, work motivation has a positive effect on employee performance, and self-efficacy has a positive effect on employee performance through work motivation as an intervening variable.